ضياع الدلالة المجازية في ترجمة أسلوب المجاز المرسل إلى اللغة الملايوية في القرآن الكريم / The Loss of Figurative Meaning in translating synecdoche in the Holy Quran to Malay Language - Haji Abdullah, Nasimah (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2019)
ملخص البحث: يعدّ أسلوب المجاز المرسل نوعا من أنواع الانتقال الدلالي؛ لأنه يشير إلى الألفاظ التي نقلت من حقائقها اللغوية إلى معانٍ أخرى لصلة ومناسبة غير صلة المشابهة، ويبدو لنا أن أسلوب المجاز المرسل الوارد في القرآن الكريم قد حظي بنصيب وافر من الاهتمام والدراسة عند اللغويين والبلاغيين والمفسرين، وكذلك لدى الخبراء الغربيين في دراسات الترجمة الحديثة؛ إذ تناولها تناولاً جاداً لا سيما ما يتعلق بمدى التكافؤ في ترجمة المجاز المرسل، فضلاً عن اقتراحهم أساليب الترجمة المختلفة بغية الوصول إلى تصدير أقرب الدلالة التي يقصدها النص الأصلي. تهدف هذه الورقة إلى الكشف عن كيفية ترجمة المجاز المرسل في القرآن الكريم إلى اللغة الملايوية وتحليلها لمعرفة مدى تطابق أسلوب الترجمة مع المعنى المراد في النص الأصلي عبر اعتبار الترجمة محاولة لتقريب المعنى، لا التبديل له، يتبع البحث المنهج الوصفي والمنهج التحليلي والمنهج المقارن. توصلت الدراسة إلى أن المترجمين يسلمون من التفسيرات غير اللازمة في إبراز الدلالات الصحيحة وتصديرها بالقدر الذي يقارب ما هي عليه في النص الأصلي العربي؛ لاعتمادهم على الترجمة الحرفية البحتة؛ الأمر الذي يؤدي إلى ضياع المعنى المجازي القرآني في النصوص المترجمة. الكلمات المفتاحية: الدلالة المجازية-المجاز المرسل-اللغة الملايوية. Abstract Synecdoche falls under the category of semantic change since it refers to a meaning which is transferred from its original to the other meanings due to a certain relation, occasion and other than the relation of similarity. It seems obvious that the Quranic synecdoche has received a great deal of interest and study among linguists, rhetoricians and interpreters. The western experts in translation studies also emphasizes the importance of an understanding of the extent of equivalence in relation to synecdoche as well as suggesting the method of translation that may attain the nearest connotation intended by the original text. As the Quranic synecdoche illustrates the mentality and environment in which the Arab society live, it is impossible to translate all of these synecdoche based solely on its literal translation due to the role of the translation of the meaning of the Quran itself is to transfer its purposes and meanings, not the words and constructs. Bearing this in mind, this paper aims to study and analyse the translation of Quranic synecdoche in Malay translations. The purpose is to understand the extent of equivalence between the methods of translation and the intended meaning as well as to suggest a better alternative method that may attain the nearest connotation intended by the original Arabic text even if not necessarily its perspicuous meaning. This study employs descriptive, analytical and comparative methods on selected Quranic translations in Malay language by Mahmoud Younis, Abdullah Basmeih and Zaini Dahlan. Based on a number of examples, the study concludes that the translators sometimes cannot deliver the precise intended meaning in their translation texts due to the sole reliance on literal translation method that cause the loss of figurative meaning in the Quranic synecdoche. Keywords: figurative meaning – synecdoche – Malay Language Abtrak Majaz Mursal tergolong dalam kategori perubahan makna kerana ia merujuk kepada makna yang telah dipindahkan daripada maksud asalnya kepada makna yang lain yang terikat dengan hubungan yang tertentu, peristiwa yang tertentu yang selain daripada kesamaan hubungan. Majaz mursal dalam Al-Quran telah mendpat perhatian yang mendalam dalam kalangan pengkaji linguistik, ilmu balaghah dan penterjemah. Pengkaji barat dalam Pengkajian Terjemahan juga menekankan kepentingan sejauh manakah kesepadanan dapat dicapai dalam menterjemahkan Majaz Mursal di samping mencadangkan kaedah terjemahan terbaik yang dapat menyampaikan maksud yang dikehendaki oleh teks asal. Memandangkan majaz mursal di dalam Al-Quran itu mencerminkan corak pemikiran dan persekelilingan kehidupan masyarakat Arab, adalah mustahil untuk menterjemahkannya secara literal kerana tujuan terjemahannya ialah untuk memindahkan tujuan dan makna, bukannya hanya perkataan dan struktur. Kajian ini bertujuan untuk mengkaji dan menganalisa terjemahan majaz mursal di dalam Al-Quran di dalam terjemahan-terjemahan pilihan Melayu. Tujuannya ialah untuk memahami sejauh manakah kesepadanan dapat dicapai oleh cara-cara terjemahan yang digunakan untuk menyampaikan maksud yang diinginkan. Ini juga adalah untuk mencadangkan cara terjemahan yang dapat menyampaikan juga maksud konotatif yang diinginkan teks asal untuk tujuan mendekatkan maksud. Kajian ini menggunakan pendekatan deskriptif, analitik dan perbandingan terhadap terjemahan-terjemahan pilihan oleh Abdullah Basmeih, mahmud Younis dan Zaini Dahlan. Di antara kesimmpulan penting kajian ialah: kadang-kadang penterjemah tidak dapat menyampaikan maksud yang dikehendaki secara tepat kerana terlalu bergantung kepada cara literal yang menyebabkan kehilangan makna majaz mursal dalam terjemahan. Oleh itu. Kata kunci: makna figuratif, majaz mursal, Bahasa Melayu